Analisis Manajemen Risiko Pembiayaan Natural Uncertaity Contracts (NUC) (Studi Pada PT Bank Syariah Mandiri Kantor Area Malang) - Hajar Hajar (Institut Ilmu Keislaman Annuqayah, 2017)
This study aims to reveal and analyze risk management developed in PT Bank Syariah Mandiri Office Area Malang by using qualitative method (qualitative research) with sub focus including: (1) identification of risk financing NUC; (2) financing risk assessment NUC; and (3) financing risk control NUC in PT Bank Syariah Mandiri Area Office of Malang. This research uses a qualitative research with a model case study approach. The data collection was done by interviewing, participant observation, and documentation. The data analysis techniques use the theory of Miles and Huberman which is performed with the three steps, namely: data reduction, data presentation, and conclusion. As for checking the validity of the data is done by: (1) checking the methodology used; (2) correcting the results of a research report; and (3) perform triangulation of sources and methods. The results showed that the financing risk management of NUC which is developed in PT Bank Syariah Mandiri Area Office of Malang that can be summed up into 11 stages, namely: (1) request for financing; (2) data collection and investigations; (3) analysis of financing; (4) review; (5) approval; (6) the collection of additional data; (7) verification; (8) the binding; (9) disbursement; (10) monitoring; and (11) risk control. However, the BSM is more emphasis on the analysis stage of financing that includes 5C, namely: character, capacity, condition, capital and collateral.